Ischemic stroke: From pathological mechanisms to neuroprotective strategies - Jiang, Yang; Liu, Zhenquan; Liao, Yan; Sun, Shuyong; Dai, Yajie; Tang, Yibo (Frontiers in Neurology, 2022)
Ischemic stroke (IS) has complex pathological mechanisms, and is extremely difficult to treat. At present, the treatment of IS is mainly based on intravenous thrombolysis and mechanical thrombectomy, but they are limited by a strict time window. In addition, after intravenous thrombolysis or mechanical thrombectomy, damaged neurons often fail to make ideal improvements due to microcirculation disorders. Therefore, finding suitable pathways and targets from the pathological mechanism is crucial for the development of neuroprotective agents against IS. With the hope of making contributions to the development of IS treatments, this review will introduce (1) how related targets are found in pathological mechanisms such as inflammation, excitotoxicity, oxidative stress, and complement system activation; and (2) the current status and challenges in drug development.